Performance Supervision and Employees’ Productivity in the Ministry of Lands, Environment and Natural Resources of Taita Taveta County, Kenya - Dorothy Ndembo Mwasawa; Lawrence Wainaina (European Scientific Journal, ESJ, 2021)
The objective of the study was to find out the effect of performance supervision on employees’ productivity in the Ministry of Lands, Environment, and Natural Resources in Taita Taveta County. Goal-setting theory and equity theory form theoretical frameworks. A descriptive research design was adopted in this study. The target population was 262 employees. Stratified random sampling was implemented to produce a sample for the study. To ascertain its level of reliability, the research instrument was pilot tested before the actual data collection. Respondents were requested to correct the contents of the questionnaire and experts were consulted to enhance the instrument’s validity. Questionnaires were issued to respondents and recollected thereafter for analysis. Sorting was conducted on the collected data. Descriptive statistics and inferential statistics were employed to analyze quantitative data. The study established that performance supervision had a positive connection with employee productivity. Therefore, the study recommended that institutions need to strive towards achieving effective supervision since it provides a safe environment for employees to reflect on their practice, as well as to develop skills and knowledge. The delivery of effective supervision is heavily dependent on the organizational context due to the dynamics surrounding the role of supervision. For the Ministry to realize high output, the outcome points in the direction of good supervision, which is believed to contribute to increased job satisfaction, increased job and organizational commitment among staff, and reduced employee turnover.